Karakteristik Seting Fisik Ruang Interaksi Warga di Kampung Bantaran Sungai Winongo Yogyakarta - Pramudito, Sidhi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2019)
Kampung is one type of living space in a city with distinctive characteristics. Yogyakarta is one of the cities in Indonesia which still has a village as part of its inhabitant' living space, one of them is a riverbank kampung. The existence of a riverbank creates a unique physical setting in the kampung, which indirectly affects the creation of inhabitant interaction space. The uniqueness and limitations of the space become interesting to be observed further as a basis for understanding local wisdom in planning future village spaces. This study uses an exploratory method, which was carried out by field observations to collect data with case studies in Kampung Gampingan on Winongo riverbank. This study aimed to determine the variations in the physical settings of space used by residents to interact in the riverbank kampung. The results of this study found several characteristics of physical settings of kampung that affect citizens in conducting interactions, as the combination of the enclosure and spatial elements for a variety of community activities. These results are expected to be used as a reference in conducting the arrangement of Kampung Gampingan as one of the slums in the city of Yogyakarta in the future that is accommodating to the characteristics of the setting of interaction spaces of its citizens.